(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
n latest days’ environmental issues such as pollution, particularly global warming and energy resource constraints, has led in extensive research into new electrical power generating methods. Thermoelectric power generators have emerged as an intriguing prospective green technology owing to its many advantages. Thermoelectric power production has a potential application in the direct conversion of waste heat energy to electrical power, when the cost of the thermal energy source is not taken into consideration. The adoption of this alternative green technologies for directly converting waste-heat energy into electrical power would also improve the overall efficiency of energy conversion systems. This article offers a viewpoint on the basic principles of thermoelectric power production, as well as a research and discussion of contemporary thermoelectric power generation with intriguing and practical uses of waste-heat electricity.